Expanded Field Theory New Axioms, Laws and Consequences (Global Journal of Science Frontier Research, 2022)
As a final result are received many models with similar shapes and content. For example, the pair in one direction of complex complementary vortex objects is a model of the electron-proton chain, and in the opposite direction is an antiproton-positron chain model. "We can not solve the problems by using the same way of thinking we used when we created them." Einstein I.